Penerapan Multiple Intelligences Perspektif Al-Qur'an Pada Mata Pelajaran Pendidikan Agama Islam Di Sma Swasta Nur Hasanah Medan - Nur Kholila Ritonga; Hasnil Aida Nasution; Nurul Hidayah (Journal of Innovative and Creativity, 2026)
This study aims to describe the implementation, relevance, and supporting and inhibiting factors of Multiple Intelligences from the Qur’anic perspective in Islamic Religious Education (PAI) at SMA Swasta Nur Hasanah Medan. The research employed a qualitative method with data collected through observation, interviews, and documentation. The findings indicate that the Qur’anic-based Multiple Intelligences approach has been integrated into the PAI learning process, encouraging students to be active, communicative, and socially skilled. Its relevance is reflected in the improvement of learning quality, emphasizing not only mastery of the material but also the development of Islamic character. Supporting factors include teacher competence, school facilities, a religious environment, and student motivation, while inhibiting factors involve limited time, differences in student ability, and a lack of learning media. Recommendations include enhancing creative teaching strategies, optimizing facilities, and providing teacher training to address existing challenges.